Sistematización de la experiencia de diseño de una metodología de medición de clima laboral y generación de planes de acción en la Empresa Parquet Los Pinos S.A. - Pino Mejía, Jenny Mercedes (2017)
This document is about experiencing the design and systematization of a method to measure the working environment and the generation of plans of action developed at the company Parquet Los Pinos SA in the city of Riobamba from 2016. The tools used to measure the working environment were a survey, applied to 35 workers from all areas of the company, and a focus group, these results have been useful to diagnose the environment in order to create the plans of action based on the factors that have shown a low punctuation. The development of this project is important due to the opportunity of putting in practice the theory and knowledge acquired in the psychology career, besides it ratifies the importance of the intervention of an occupational psychologist within a company. The main purpose and conclusion of this document is to increase the motivation of the workers and generate a positive impact on them and on the company.